Comparative and International Education as a Way to Strengthen Internationalisation in Teacher Education Programmes at Universities in Africa (Teacher Education through Flexible Learning in Africa (TETFLE), 2024)
One lacuna in teacher education programmes at universities in Africa is a lack of internationalisation. This is a position paper, using the method of comparative and international education. The paper argues that imbuing teacher education programmes at universities in Africa with comparative and international education is an obvious way to counter such detrimental trends of parochialism, universities appointing their alumni, an inward orientation and to effect internationalisation in such programmes. This is particularly significant at this point, when the constraints brought about by the COVID-19 pandemic have rendered many of the other conventional means of internationalising higher education difficult or impossible. The article concludes comparative ad international education courses in teacher education programmes fully serve a host of purposes. These include description of education systems, understanding of education systems, improvement of education practice (both at policy and at classroom level), applying the comparative method to investigate or illuminate education issues, and furthering of the philanthropic ideal. Furthermore, such courses appear to be ideally suited to bring about much-needed internationalisation in such programmes. Being part of an internationalisation drive, it may have several additional benefits related to the countering of Northern hegemony in education, and shaping the course of the decolonisation of education drive.